The Influence of Service Quality on Customer Loyalty Mediated by Customer Satisfaction - Karo Karo, Gilberte; Yuniarinto, Agung (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the indirect effect of service quality on customer loyalty through customer satisfaction as a mediating variable at Inama Laundry. Design/methodology/approach – This study employs a quantitative research design using a mediation analysis approach. The sample consists of at least 130 respondents, selected in accordance with the rule-of-thumb sample size criteria. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Findings – The results indicate that customer satisfaction has a positive and significant effect on customer loyalty. Service quality also has a positive and significant indirect effect on customer loyalty through customer satisfaction. Furthermore, customer satisfaction partially mediates the relationship between service quality and customer loyalty, indicating that service quality influences loyalty both directly and indirectly via satisfaction. Originality/value – This study contributes to service marketing literature by clarifying the mediating role of customer satisfaction in the relationship between service quality and customer loyalty in the laundry service industry. The findings provide practical implications for service providers in improving service quality to enhance customer satisfaction and strengthen long-term loyalty.